To Power, a Dictator: An Evaluation of Midwestern Religious and Secular News About Early Nazi Germany - Edwards, Austin (My University, 2023)
News media has the unique ability to shape the perceptions of a mass audience. Writing or relaying messages directly influences the collective consciousness of the audience by painting a portrait of events. The pre-war coverage of Nazi Germany is no exception to this rule. This paper aims to evaluate the coverage of midwestern newspapers and the perceptions that their respective audience would have had of Nazi Germany. This includes two religious newspapers, The Jewish Press of Nebraska and the Catholic Advance of Kansas, and two secular newspapers, The Lincoln Journal-Star of Nebraska and The Kansas City Star of Missouri. In reading these papers, one finds that they each present very different interpretations and perceptions of what exactly the Nazi state was. The Kansas City Star saw Germany as an unstable nation whose leader was scarcely competent but who eventually evolved into a tyrannical and iron-fisted dictator. Lincoln Journal Star was concerned with the concept of reasonability that caused it to question any and all actions taken. The religious papers both concerned themselves with their faiths within Germany, with The Catholic Advance focusing on persecution of Catholics and the thoughts of the Vatican and The Jewish Press opting to focus on Nazi aggression against Jews as well as protests and events within the United States hoping to raise awareness of Nazi atrocities.